Distribution of unit mass on one fractal self-similar web-type curve - M. V. Pratsiovytyi; I. M. Lysenko; S. P. Ratushniak; O. A. Tsokolenko (Математичні Студії)
In the article, we study structural, spectral, topological, metric and fractal properties of distribution of complex-valued random variable $τ=\sum\nolimits_{n=1}^{∞}\frac{2ε_{τ}}{3^n}\equivΔ^g_{τ_1...τ_n...}$, where $(τ_n)$ is a~sequence of independent random variables taking the values $0,1,…,6$ with the probabilities $p_{0n}$, $p_{1n},…,p_{6n}$; $ε_{6}=0$, $ε_0$, $ε_1,…,ε_5$ are 6th roots of unity.